5G base-station antenna array - Li, Tianqi (Nanyang Technological University, 2021)
2020 is called the first year of 5G. Compared with the previous wireless communication, 5G needs to use new frequency bands. This project is a base-station antenna array designed for the new 5G frequency band. [1] Microstrip antenna is selected because it is easy to fabricate, and the cost is low. However, there is some disadvantage such as low gain and narrow bandwidth. On the other hand, these disadvantages can be overcome by designing as antenna arrays. Therefore, the main task of this project is to design antenna arrays to increase the antenna gain and bandwidth. Center frequency will be 5.2GHz. In addition, I will use High-Frequency Structural Simulator (HFSS) software to design and simulate. Performance of the antenna are analyzed by the parameters such as reflection coefficient, radiation pattern, gain pattern and directivity. Furthermore, based on the simulation result, these 2 arrays will be fabricated out. Hence, with the fabrication antennas, the above data can be compared with the simulation result and therefore, the project are completed.